Water permeability of foamed concrete - Wan Ibrahim, Mohd Haziman (2004)
This study focused on the compressive strength and water permeability of foamed concrete. Two types of foamed concrete mix with density 1500 kg/m3 and 1700 >5 kg/m were experimented Timber industrial ash (HA) were used as the partial cement replacement material, replacing 10% of Ordinary Portland cement (OPC) in the mix design. The test cubes were 150 mm X 150 mm X150 mm size subjected to wet-cured and air cured for up to 28 days. The density, compressive strength development and water permeability of the TIA foamed concrete were determined to compare with the control mix (without TIA). The test method adopted based on DIN 1048 was used to determine the water permeability of foamed concrete at 28 days. Compressive strength was determined at 3 days, 7 days and 28 days. It was found that the air-cured specimens achieved a higher compressive strength and lower water permeability compared with the wet-cured specimens. Foamed concrete with 10% HA reduced the water permeability with a lower compressive strength at 28 days. The preliminary result indicated that HA has potential to reduce the water permeability of foamed concrete